2019
DOI: 10.1002/jocb.407
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing and Enhancing Creativity of Nursing Students in Taiwan: A Quasi‐Experimental Study

Abstract: Creativity and innovation are considered important measures of core competence in Taiwan for students of all levels, including nursing students. Integrating creativity with interdisciplinary teaching modules could increase creativity for nursing students; however, this has not been empirically determined. The purpose of this study was to determine if incorporating interdisciplinary teaching into a teaching for creativity module (TCM) could enhance creative thinking and creative abilities of nursing students. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The average score of the group who thinks innovative thinking is not necessary is higher. In a study evaluating the effectiveness of creativity courses in nursing students, the importance of developing creative thinking skills and integrating creative teaching techniques into nursing education was emphasized [31]. While creativity requires an idea, interpretation or solution that solves a problem, innovations involve the application of that idea [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The average score of the group who thinks innovative thinking is not necessary is higher. In a study evaluating the effectiveness of creativity courses in nursing students, the importance of developing creative thinking skills and integrating creative teaching techniques into nursing education was emphasized [31]. While creativity requires an idea, interpretation or solution that solves a problem, innovations involve the application of that idea [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The study results provide practical recommendations that for Strengthening the role of teachers in efforts to develop the character of reading fondness, every teacher can do so in all subjects. In the learning process, the teacher can develop a character reading fondness by designing learning objectives that are nurturing (Liu, 2020;Schultz, 2015). The character of reading fondness is one of the students' potentials that can be developed for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that the creative thinking teaching method has a significant impact on all aspects of creative tendency (Chen, 2003 ; Hung, 2004 ), but there are also studies show that there is no significant impact (Liu et al, 2020 ). It can be seen that the creative thinking teaching method can affect students' creative thinking ability, but it is not clear whether the creative thinking teaching method can significantly improve students' creative tendency.…”
Section: Methodsmentioning
confidence: 99%